(untitled) (Религиски дијалог и соработка, 2023)
The modern world citizen today rejects Christian morality as retrograde. Thus, a modern, syncretic, and global alternative to the human self emerges – New Age movement, which is becoming more widespread and sought after by quickly solving life’s problems and ensuring personal happiness. The cultural Christianity of the Bulgarians facilitates the spread of New Age beliefs and practices: the historically established “pagan Christianity” of the Bulgarians is manifested by latent religiosity, dualistic, rich mythological demonology, and oral patriarchal tradition. At first sight, Bulgarian New Age is a liberal religion (according to Peter Beyer): tolerant and ecumenical, with the aim of including more people to work for the benefit of the world community. But more in-depth research reveals that the proximity in the doctrines of Bulgarian New Age and Bulgarian Orthodoxy in everyday life allow their conflict-free coexistence. Additionally, the sociological interpretation of Mark Satin’s quadrant shows that, unlike the Western New Age, Bulgarian New Age beliefs and practices represent a conservative response to life’s challenges, closer to monolithic institutions than biolithic ones: “the path of freedom = the path of suffering = the path of redemption”. Therefore, both the Bulgarian “high” New Age and Bulgarian Orthodoxy are two conservative responses in a globalized and secularized world. Interpreted through Orthodox theology, Bulgarian New Age is a commune movement: “from below”, organic, informal, non-legal, non-institutionalized, non-hierarchical. In functional terms, it represents a “synthetic metanarrative” of traditional Bulgarian Orthodoxy and particularly Petar Danov’s teaching, which derives its strength from the claim for Bogomil heritage and avoiding the “confessional curse”, and the social change needs time and hard self-work.